Analisis Perbandingan Kinerja Keuangan dan Return Saham sebelum dan setelah Merger dan Akuisisi dengan Good Corporate Governance sebagai Variabel Moderasi - Sabrina Salsabila Azzahra; Hari Setiono; Nurdiana Fitri Isnaini (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The aim of this research is to analyze the comparison of financial performance and stock returns before and after mergers and acquisitions which are moderated by good corporate governance. This research applies comparative quantitative methods, using secondary data. A population of 21 companies that have carried out merger and acquisition activities were registered with the KPPU in 2021 and listed on the IDX during the 2019-2023 period. A sample of 11 companies was obtained with a 4 year observation span using the purposive sampling method. The data analysis used was IBM SPSS version 27 software with hypothesis testing, namely paired sample t-test, t test, R2 test, and MRA test. The research results show that the ROA, CR, DER, TATO, EPS and Stock Return variables do not show differences before and after carrying out mergers and acquisitions. The proportion of independent board of commissioners cannot moderate the influence of ROA, CR and EPS on merger and acquisition performance. The proportion of independent board of commissioners can moderate the influence of DER, TATO, and Share Return on merger and acquisition performance.